2022
DOI: 10.15678/eber.2022.100109
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial social identities and nascent entrepreneurial behaviour: Mediating role of entrepreneurial self-efficacy

Abstract: The objective of this article is to investigate the influence of entrepreneurial social identities (Darwinian, missionary, and communitarian) on nascent entrepreneurial behaviour with the mediating effect of entrepreneurial self-efficacy. Research Design & Methods:The study is based on a research sample of 455 students from public sector universities of Punjab, Pakistan. The survey questionnaire was developed along with PLS-SEM partial least squares structural equation modelling technique to examine the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…A small family business is controlled by the founder or his descendants across generations ( Ahmad et al, 2018 ). Each descendant has different entrepreneurial, cognitive capabilities and vision to rationalize complex issues like succession ( Murad et al, 2022 ). An entrepreneur’s attitude, behavior, and cognitive capabilities are the reflections of an individual’s personality traits ( Zicat et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A small family business is controlled by the founder or his descendants across generations ( Ahmad et al, 2018 ). Each descendant has different entrepreneurial, cognitive capabilities and vision to rationalize complex issues like succession ( Murad et al, 2022 ). An entrepreneur’s attitude, behavior, and cognitive capabilities are the reflections of an individual’s personality traits ( Zicat et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The students could identify business ideas by looking at the needs and want of the community by identifying and exploring potential opportunities. Numerous studies have found that entrepreneurship education positively equips entrepreneurs and those interested in entrepreneurship with the necessary knowledge and skills (Gieurea et al, 2020;Kuratko & Morris, 2017;Murad et al, 2022). Therefore, incorporating entrepreneurship education into tertiary-level education can improve knowledge and increase students' ability to recognize opportunities and gather pertinent information, enabling them to capitalize on potential opportunities and pursue entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these emotions prevent individuals from engaging in entrepreneurial activities. Furthermore, emotions are formed due to external stimuli that shape individual experiences (Celik & Calik, 2022;Gogan & Belinsky, 2022;Murad et al, 2022). In other words, positive emotions can be elicited if the experience acquired through entrepreneurship education is meaningful, as students then may acquire a higher emotional capacity to face the obstacles and pressures of entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…More studies are needed to accurately capture differences in probability discounting; for example, conjoint designs could give many options for manipulating desirability and feasibility characteristics. Murad et al (2022) conducted an investigation into the association between early-stage entrepreneurial practises and entrepreneurial social identities, with a particular focus on entrepreneurial self-efficacy. The research comprised a sample of 455 undergraduate students who were enrolled in public universities located in the province of Punjab, Pakistan.…”
Section: Empirical Reviewmentioning
confidence: 99%